The prodigal daughter - Harrison, Mette Ivie, 1970- (Harrison, Mette Ivie, 1970- Linda Wallheim mystery., 2021)
"Linda Wallheim, who is increasingly jaded with the Mormon church, has begun marriage counseling with her bishop husband, Kurt, hoping to reconcile their household and philosophical disagreements. On other days, Linda occupies herself with happier things, like visits to see her five grown sons and their families. When Linda's eldest son, Joseph, tells her his infant daughter's babysitter, a local teenager named Sabrina Jensen, has vanished, Linda can't help but ask questions. Her casual inquiries form the portrait of a girl under extreme pressure from her parents to be the perfect Mormon daughter, and it eventually emerges that Sabrina is the victim of a terrible crime at the hands of her own classmates-including the high school's academic and athletic superstars. Linda's search for Sabrina will lead her to the darker streets of Utah and once again cause her to question whether the Mormon community's most privileged and powerful will be called to task for past sins"--